2021
DOI: 10.3390/brainsci11060760
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute COVID-19 Symptoms, a Potential Link with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: A 6-Month Survey in a Mexican Cohort

Abstract: The aim of this study was to describe the clinical evolution during 6 months of follow-up of adults recovered from COVID-19. We tried to determine how many met the definition of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). A total of 130 patients (51.0 ± 14 years, 34.6% female) were enrolled. Symptoms were common, participants reported a median number of 9 (IQR 5–14) symptoms. Fatigue was the most common symptom (61/130; 46.9%). Patients with fatigue were older 53.9 ± 13.5 years compared with 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 39 publications
5
77
0
9
Order By: Relevance
“…A retrospective analysis reported that 85.3% of 231 COVID-19 survivors gathered from the Genome Database of Latvian Population national biobank reached the threshold for ME/CFS diagnosis, with three or more long-term ME/CFS-like symptoms persisting at 6 months follow-up [ 185 ]. A single-center prospective longitudinal study found that only 13% of 130 patients with moderate-to-severe COVID-19 pneumonia met the criteria for ME/CFS 6 months after discharge [ 186 ]. In a small, single-center pilot study, ME/CFS-like features were found in 27% of 37 COVID-19 survivors, six months after recovery, with no difference in clinical inflammation, lung function, serum neurofilament light chain (a biomarker of axonal damage), and objective cognitive testing when comparing patients with versus without ME/CFS-like features [ 187 ].…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective analysis reported that 85.3% of 231 COVID-19 survivors gathered from the Genome Database of Latvian Population national biobank reached the threshold for ME/CFS diagnosis, with three or more long-term ME/CFS-like symptoms persisting at 6 months follow-up [ 185 ]. A single-center prospective longitudinal study found that only 13% of 130 patients with moderate-to-severe COVID-19 pneumonia met the criteria for ME/CFS 6 months after discharge [ 186 ]. In a small, single-center pilot study, ME/CFS-like features were found in 27% of 37 COVID-19 survivors, six months after recovery, with no difference in clinical inflammation, lung function, serum neurofilament light chain (a biomarker of axonal damage), and objective cognitive testing when comparing patients with versus without ME/CFS-like features [ 187 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, some observational studies investigated the persistent symptoms in hospitalized COVID-19 survivors beyond 3 months [9][10][11][12][13]. Ghosn and colleagues analyzed 1137 hospitalized survivors (of which 288 admitted to the intensive care unit) and found that 60% had at least one symptom at 6 months, most frequently fatigue, dyspnea, joint pain, and muscle pain [11].…”
Section: Discussionmentioning
confidence: 99%
“…Garrigues and colleagues assessed 120 survivors through telephone surveys after a mean of 111 days after admission either to the hospital ward unit (n = 96) or to the intensive care unit (n = 24) and documented that 54.2% had fatigue, 39.6% had dyspnea, 14.6% had cough, 14.6% had anosmia, and 9.4% had ageusia in the hospital ward unit group [9]. González-Hermosillo and colleagues assessed 130 survivors through telephone surveys and reported that 46.9% had fatigue, 43.8% joint pain, 42.3% had dyspnea, 36.2% muscle pain, 6.9% had anosmia, and 5.4% had ageusia at 6 months [10]. Fortini and colleagues assessed 59 survivors after a median of 123 days after discharge from the hospital ward unit and observed that 42.4% had fatigue, 37.3% had dyspnea, 16.9% had ageusia, 15.2% had anosmia, 11.9% had cough, 8.5% joint pain, and 8.5% myalgia [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schätzungsweise 836.000 bis 2,5 Mio. Amerikaner leiden an ME/CFS, und etwa 90 % der Menschen mit ME/CFS wurden nicht diagnostiziert (CDC) [ 11 ]. Die Pathologie von ME/CFS ist nicht bekannt: Eine multifaktorielle Genese und eine Fehlregulation mehrerer Kreisläufe als Reaktion auf einen bestimmten Auslöser wird diskutiert.…”
Section: Neurologische Manifestationenunclassified